2018
DOI: 10.3892/ijmm.2018.3469
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis is associated with oxygen-glucose deprivation/reoxygenation-induced Sertoli cell death

Abstract: Sertoli cell death contributes to spermatogenesis impairment, which is associated with male infertility. Testicular ischemia‑reperfusion (I/R) injury induces the cell death of germ cells and Sertoli cells, whereas inhibition of cell death ameliorates acute testicular I/R damage. The aim of the present study was to investigate the mechanism of I/R stress-induced cell death in TM4 cells. Oxygen‑glucose deprivation and reoxygenation (OGD/R) was demonstrated to induce I/R injury and cell death in TM4 cells. Cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 64 publications
(113 reference statements)
2
49
0
Order By: Relevance
“…Consistently, the up-regulation of USP22 has been proven to promote intestinal cell proliferation and tissue regeneration following I/R or hypoxia/reoxygenation, thus exerting a similar protective function on intestinal I/R injury (Ji et al, 2019). Ferroptosis is involved in the oxygen-glucose deprivation/reoxygenation-induced Sertoli cell death, commonly characterized by elevated iron and lipid reactive oxygen species levels in I/R injury and depleted GSH (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Consistently, the up-regulation of USP22 has been proven to promote intestinal cell proliferation and tissue regeneration following I/R or hypoxia/reoxygenation, thus exerting a similar protective function on intestinal I/R injury (Ji et al, 2019). Ferroptosis is involved in the oxygen-glucose deprivation/reoxygenation-induced Sertoli cell death, commonly characterized by elevated iron and lipid reactive oxygen species levels in I/R injury and depleted GSH (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Ferroptosis, a new regulated cell death identified by Brent R. Stockwell's lab in 2012, is mediated by an iron dependent accumulation of lipid reactive oxygen species (ROS) . Study by Li et al showed that ferroptosis is a pervasive and dynamic type of cell death induced by Oxygen-glucose deprivation and reoxygenation injury in Sertoli cells [28], Elizabeth G explored the contribution of ferroptosis to the demise of germline cells during periods of acute stress in vivo [29]. Previous studies have verified that the lethal lipid peroxidation reaction is accelerated by intracellular iron in the germ cells, whereas other divalent cationic metals have no effect [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of SLC40A1 by RNAi or HAMP-mediated downregulation of SLC40A1 promotes erastin-induced ferroptosis, while ponasterone (a SLC40A1 inducer) impedes this process (Geng et al, 2018). Similarly, the knockdown of SLC40A1 enhances oxygen-glucose deprivation and reoxygenation (OGd/R)-induced ferroptosis in testicular ischemia-reperfusion (I/R) injury sertoli cells (Li L. et al, 2018). In contrast, the overexpression of SLC40A1 or treatment with ponasterone rescues OGd/R-induced ferroptosis by decreasing iron accumulation in sertoli cells (Li L. et al, 2018).…”
Section: Solute Carrier Family 40 Membermentioning
confidence: 99%